A brief note on the human visceral skeleton - An evolutionary perspective - Baruch Arensburg; Victor Belkin; Anne-Marie Tillier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
A review of the visceral skeleton whose origin is in the branchial arches is reported here. It refers to bones, muscles and ligaments of relevant anatomical areas (ear ossicles, basicranium and mandible). The phylogenetic role of visceral skeleton components in the classification of prehistoric human remains has been analyzed by many scholars. It seems that the large morphological variation of these components among human groups makes their taxonomic significance questionable.